Study on the preference between online and printed journals of Ateneo de Manila University students - Abellon, Jeffrey C.; Pascua, Sonia M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2017)
This undergraduate thesis checked the preference between online and printed journals of Ateneo de Manila University (ADMU) Rizal Library users. The factors involved had been analyzed to determine the needs of the users in terms of various surveys conducted and interviews. The purpose of this study was to assess the awareness and preference of the library users towards the journal collection of Rizal library. The gathered data came from the interviews of three different library staff of ADMU who are reasonably familiar with the journal collection together with a total of 250 respondents who willingly answered the online and printed versions of the survey questionnaire. The data revealed that the library users are comparatively aware and familiar of the journal collection as exhibited by 42% of the total respondents. In regard to the preference, over 90% of the respondents said that they prefer online journals over printed journals with consideration to factors like ease of access, it can be used all over the campus, it saves cost on printing, etc.
Thesis
Keywords: Ateneo de Manila University -- Students; Electronic journals -- User studies -- Philippines; Periodicals Periodicals -- Use studies -- Philippines